Avaliação dos efeitos de proteínas larvicidas contra Aedes aegypti sobre o peixe-zebra (Danio rerio): toxicidade aguda em embriões e larvas e inibição de proteases intestinais - Gonçalves, Íris Flávia de Sousa (2022)
For several years, the presence of compounds with insecticidal properties against the dengue vector, the Aedes aegypti mosquito, has been investigated in the flora of the Caatinga. One of these compounds is the trypsin inhibitor obtained from seeds of the plant species Leucaena leucocephala (LTI). LTI is capable of delaying the development and causing mortality of larvae, in addition to acting in a deleterious way on the hatching of mosquito eggs. This inhibitor also potentiates the activity of the bacterium Bacillus thuringiensis (Bt), which is one of the most studied biopesticides. Combining their biochemical and insecticidal properties, these molecules are excellent candidates for the development of phytoinsecticides. However, during the development of these products, safety assessment for use in the aquatic environment is an important step, especially evaluating their effect on non-target organisms. In this context, the zebrafish (Danio rerio) is a model vertebrate with numerous advantages for this type of study, among them is the sensitivity of the early stages of its life to environmental stressors. Thus, the present work aimed to evaluate the effects of larvicidal proteins against Ae. aegypti, LTI and Bt protoxins, to the zebrafish model organism regarding the assessment of toxicity to its early life stages and the presence of inhibitory effects of LTI on intestinal proteases of this fish. For this, an acute toxicity test of LTI and Bt protoxins, isolated and combined, was performed in zebrafish embryos and larvae. In addition, the possible interaction between LTI and zebrafish trypsin was investigated with the aid of computational tools, as well as the intestinal extract of adult zebrafish of both sexes was obtained to evaluate the presence of trypsin inhibitory activity of the LTI to infer possible damages to the digestive process, nutrition and development of fish exposed to this formulation. The results showed that concentrations of LTI (250 mg/L), Bt (0.13 mg/L) and LTI + Bt (250 mg/L + 0.13 mg/L), 10 times higher than those with insecticidal action, did not cause deaths nor induce morphological changes during embryonic and larval development (3 to 144 hpf) of zebrafish. The molecular docking analysis showed the interaction between LTI and zebrafish trypsin through hydrophobic interactions, in addition to a hydrogen bond between Arg58 of LTI and His23 of trypsin. In fact, LTI (0.1 mg/mL) was able to inhibit in vitro the trypsin activity of intestinal extracts from female and male fish by 83 and 85%, respectively, while the mixture LTI and Bt (both at a concentration of 0.1 mg/mL) promoted inhibition of 69 in females and 65% in males. This finding suggests a potential anti-nutritional effect of LTI and its mixture with Bt to non-target organisms at concentrations close to those that have larvicidal action. In general, these data lead to the conclusion that, in a natural environment, this larvicidal mixture can have deleterious effects on aquatic organisms, especially those with protein digestion dependent on trypsin-like enzymes.